Do weight bearing radiographs estimate the stability of an isolated distal fibula fracture?. Issue 3 (14th September 2018) - Yousaf, Sohail; Hay, Daniel
Category: Trauma Introduction/Purpose: Differentiating stable isolated fibula fractures consistent with supination external rotation (SER) II ankle fractures from unstable SER IV fractures is essential in determining the need for surgical stabilisation. Stress radiographs are usually required to assess stability including gravity stress views (GSV) and external rotation views (ER). There is no clear consensus as to which modality is most useful to determine stability in a fracture clinic or emergency setting. In last, few years clinical uncertainty about the reliability has led researcher to focus on weight bearing radiographs (WB) .We aim to review recent literature regarding reliability of WB radiographs to estimate the stability of supination external rotation ankle fractures. Methods: A systematic review of the literature relating to radiological assessment of stability of supination external rotation ankle fractures was conducted according to PRISMA guidelines. The systematic review was prospectively registered with PROSPERO. It involved the following steps: Researching the question-Do weight bearing radiographs estimate the stability of an isolated distal fibula fracture? Setting inclusion and exclusion criteria-All English language articles published in the including any Randomised controlled trials (RCT's) and cohort studies. Data collection)– A literature search of Medline (PubMed), the Cochrane Bone, Joint, and Muscle Trauma Group trial register, the Cochrane central register of controlled trials, Embase and CINAHL was undertaken. The grey literature was searched. Key terms 'supination external rotation fracture', 'stability'. Other variations to the key words were 'weight bearing', "axial load", 'stress x-rays', 'systematic reviews' and 'meta-analysis'. Results: A total of six studies met the inclusion criteria including 601 patients. No previous systematic review on stress radiographs including weight bearing was published. All studies concluded weight bearing radiographs is an easy, pain-free, safe and reliable method to estimate stability of isolated distal fibula fractures. No serious concerns or complications were reported. Conclusion: The evidence base contained many methodological limitations and most of the evidence was either level III or IV, and so any conclusion drawn from the research must be done so with caution. The studies suggest that GSV overestimates the instability which should be assessed with studies should focus on randomized controlled trials with narrow range of clinically useful outcome measures.